SARS-CoV-2 Infection in Children - Lu, Xiaoxia; Zhang, Liqiong; Du, Hui; Zhang, Jingjing; Li, Yuan Y; Qu, Jingyu; Zhang, Wenxin; Wang, Youjie; Bao, Shuangshuang; Li, Ying; Wu, Chuansha; Liu, Hongxiu; et al. (The New England journal of medicine, 2020)
In this report, investigators in Wuhan, China, describe the spectrum of Covid-19 illness in children under the age of 16 years. Of 1391 children assessed and tested over a period of 4 weeks, 171 (12.3%) were confirmed to have SARS-CoV-2 infection.